2021
DOI: 10.3389/fncel.2021.788262
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Loss of the Glutamate Transporter GLT-1 Promotes Excitotoxic Injury in the Hippocampus

Abstract: GLT-1, the major glutamate transporter in the mammalian central nervous system, is expressed in presynaptic terminals that use glutamate as a neurotransmitter, in addition to astrocytes. It is widely assumed that glutamate homeostasis is regulated primarily by glutamate transporters expressed in astrocytes, leaving the function of GLT-1 in neurons relatively unexplored. We generated conditional GLT-1 knockout (KO) mouse lines to understand the cell-specific functions of GLT-1. We found that stimulus-evoked fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 139 publications
0
15
1
Order By: Relevance
“…Neuronal GLT-1 knockout is sufficient to produce late-onset cognitive deficits [ 63 ]. However, while axonal GLT-1 is known to contribute to presynaptic energy supply [ 64 ] and its presence can help protect from excitotoxic damage [ 65 ], its contribution to overall extracellular glutamate dynamics is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal GLT-1 knockout is sufficient to produce late-onset cognitive deficits [ 63 ]. However, while axonal GLT-1 is known to contribute to presynaptic energy supply [ 64 ] and its presence can help protect from excitotoxic damage [ 65 ], its contribution to overall extracellular glutamate dynamics is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Five human EAATs have been identified: EAAT1-5: glutamate−aspartate transporter (GLAST/EAAT1), glutamate transporter (GLT/EAAT2), excitatory amino acid carrier (EAAC/EAAT3), and excitatory amino acid transporters 4 and 5 (EAAT 4 and EAAT5) ( 163 ) ( Figure 1 ). EAAT1-3 are high-capacity glutamate transporters that play an important role in the regulation of the vulnerability to excitotoxicity modulating accumulation of glutamate, its receptors activation, and its metabolic homeostasis ( 171 , 172 ). In addition, EAATs also serve as anion channels.…”
Section: Glutamate Signaling In Cancer Of Non-neural Organsmentioning
confidence: 99%
“…This is in agreement with another study demonstrating that extracellular glutamate concentrations were decreased in synGLT-1 KO synaptosomes, indicating that glutamate homeostasis is regulated by GLT-1 ( McNair et al, 2019 ). Moreover, it was reported that a hippocampal injury develops because of loss of neuronal GLT-1 ( Rimmele et al, 2021 ). Importantly, GLT-1 is more highly localized in the forebrain than in the cerebellum ( Holmseth et al, 2012 ).…”
Section: Role Of Glutamate Transporters In Glutamate Homeostasismentioning
confidence: 99%
“…It is important here to note that GLT-1 is expressed in presynaptic terminals of glutamatergic neurons as well as in astrocytes. Rimmele et al (2021) provided evidence that the GLT-1 expressed in presynaptic neuronal terminals serves an important role in regulation of vulnerability to excitotoxicity. Stimulus-evoked field extracellular postsynaptic potentials recorded in the CA1 region of the hippocampus of conditional GLT-1 knockout (KO) mouse lines were normal in the astrocytic GLT-1 KO with elevated glutamate and were reduced in the neuronal GLT-1 KO but with normal glutamate accumulation.…”
Section: Evidence That Hyperglutamatergic State Causes Neuroexcitotox...mentioning
confidence: 99%